Molecular cloning and expression of a purine-specific N-ribohydrolase from Trypanosoma brucei brucei. Sequence expression and molecular analysis - Pelle, Roger; Schramm, V.L.; Parkin, D.W. (Elsevier, 1998)
N-Ribohydrolases, including the inosine-adenosine-guanosine-preferring (IAG) nucleoside hydrolase, have been proposed to be involved in the nucleoside salvage pathway of protozoan parasites and may consitute rational therapeutic targets for the treatment of these diseases. Reported is the complete sequence of the Trypanosoma brucei brucei iagnh gene, which encodes IAG-nucleoside hydrolase. The 1.4 kilobase iagnh cDNA contains an open reading frame of 981 base pairs, corresponding to 327 amino acids. The iagnh gene is present as one copy/haploid genome and is located on the size-polymorphic pair of chromosome III or IV in the genome of T. b. brucei. In Southern blot analysis, the iagnh probe hybridized strongly with Trypanosoma brucei gambiense, Trypanosoma brucei rhodesiense, Trypanosoma evansi, Trypanosoma congolense, and Trypanosoma vivax and to a lesser extent, with Trypanosoma cruzi genomic DNA. The iagnh gene is expressed in blood-stream forms and procyclic (insect) life-cycle stages of T. b. brucei. There are no close amino acid homologues of LAG-nucleoside hydrolase outside bacterial, yeast, or parasitic organisms. Low amino acid sequence similarity is seen with the inosine-uridine-preferring nucleoside hydrolase isozyme from Crithidia fasciculata. The T. b. brucei iagnh open reading frame was cloned into Escherichia coli BL21 (DE3), and a soluble recombinant LAG-nucleoside hydrolase was expressed and purified to > 97 percent homogeneity. The molecular weights of the recombinant LAG-nucleoside hydrolase, based on the amino acid sequence and observed mass, were 35,735 and 35,737, respectively. The kinetic parameters of the recombinant LAG-nucleoside hydrolase are experimentally identical to the native IAG-nucleoside hydrolase.